2020
DOI: 10.1590/1518-8345.3370.3296
|View full text |Cite
|
Sign up to set email alerts
|

Drug use by men admitted to a psychiatric hospital*

Abstract: Objective: to assess risk related to drug use in men admitted to a psychiatric hospital and to identify associations with sociodemographic, socioeconomic variables, and risk conditions. Method: a cross-sectional study with the application of a screening test in 209 participants hospitalized for mental and behavioral disorders due to the use of psychoactive substances. Statistical analysis was performed using descriptive statistics and adjustment of a binary logistic regression model for moderate or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
7
0
5
Order By: Relevance
“…The role that religion and spirituality play in the cessation of criminal behavior and the use of PASs is not yet fully understood, but suggests a relatively high importance in substance use in the prison environment, particularly in relation to alcohol and cocaine 40 . Another Brazilian study also found that inhaled cocaine, at moderate and high levels, had a statistically significant association with the variables not professing religion, risky sexual behavior, age 18 to 34 years, and living with a drug user 41 .…”
Section: Discussionmentioning
confidence: 86%
“…The role that religion and spirituality play in the cessation of criminal behavior and the use of PASs is not yet fully understood, but suggests a relatively high importance in substance use in the prison environment, particularly in relation to alcohol and cocaine 40 . Another Brazilian study also found that inhaled cocaine, at moderate and high levels, had a statistically significant association with the variables not professing religion, risky sexual behavior, age 18 to 34 years, and living with a drug user 41 .…”
Section: Discussionmentioning
confidence: 86%
“…Porém, sabe-se que o curso evolutivo seguido pelas experiências com o álcool e drogas é desconhecido, indicando que a prevenção ativa no início do consumo pode significar o único meio eficaz de prevenção. 10,12 O perfil etário encontrado neste estudo corresponde à idade economicamente ativa, pois a maioria dos casos foi notificada em indivíduos que referiram estar empregados -apesar da precariedade dos contratos de trabalho e da elevada informalidade. No entanto, a situação no mercado de trabalho foi a variável com maior número de informações não registradas, possivelmente justificadas pela recusa da informação do paciente durante a abordagem de coleta de dados à internação ou pela ausência desse questionamento ao paciente.…”
Section: Discussionunclassified
“…5 Mesmo com as políticas públicas voltadas para essa problemática, os pacientes apresentam alta variabilidade de resposta às intervenções e às taxas igualmente elevadas de recidivas, necessitando de internações hospitalares. 11,12 O consumo de álcool está associado diretamente ao aumento do risco de hospitalização em grande parte da população brasileira, atingindo cerca de três milhões de mortes (5,3%) anuais, além de sequelas temporárias ou permanentes. 13 Um estudo com 611 admissões em uma Unidade de Terapia Intensiva geral nos Estados Unidos informou que as drogas foram responsáveis por 28% das admissões hospitalares e 39% dos custos hospitalares.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…O papel que a religião e a espiritualidade desempenham na cessação do comportamento criminoso e do uso de SPAs ainda não foi totalmente compreendido, mas sugere uma importância relativamente alta no uso de substâncias no ambiente prisional, particularmente em relação ao álcool e à cocaína (40) . Outro estudo brasileiro também identificou que a cocaína inalada, nos níveis moderado e elevado, apresentou associação estatística significativa com as variáveis não professar religião, ter comportamento sexual de risco, ter idade de 18 até 34 anos e conviver com usuário de drogas (41) .…”
Section: Discussionunclassified